Improving productivity in block/panel caving through dynamic confinement of semi-autonomous load-haul-dump machines. Issue 8 (14th September 2022) - Espinoza, José Pablo; Mascaró, Mauricio; Morales, Nelson; Ruiz Del Solar, Javier
ABSTRACT: The incorporation of autonomous equipment is fuelling a revolution in mining, but it poses operational challenges due to potential hazardous interactions between humans and the autonomous machinery. For this reason, block and panel caving mines operate under a static confinement policy that stops all autonomous LHDs when workers must enter the production area, thus having a huge negative impact on productivity. To address this challenge, we propose two dynamic confinement policies, and we model them using discrete event simulation. Results show that the dynamic moderate/intensive policies may lead to increases in production of 35%/45% when compared with the static policy.